(untitled) (Medical Forum Monthly, 2024)
Objective: To construct a foreseeable connection of total testosterone with lipid profile in middle aged healthy men. Study Design: Analysis / cross sectional study. Place and Duration of Study: This study was conducted at the Dow University of Health Sciences Karachi for duration of nine month from April 2012 to January 2013. Materials and Methods: Two hundred disease free nonsmoker males of 30 to 50 years of age were enrolled for this study, total testosterone value was estimated by Chemiluminescence assay method and fasting lipid profile which includes cholesterol, triglyceride, high density lipoprotein (HDL) and low density lipoprotein (LDL) were tested in Hitachi 902 auto analyzer by photometry technique. Mean differences of all the lipid parameters in between the two groups of testosterone were computed by independent sample T test. Correlation between total testosterone and fasting lipid parameters was assessed by Pearson correlation. Multivariable linear regression was also applied to predict the change in the levels of lipid profile parameters on the basis of per unit rise in total testosterone level. Results: In this study the mean (± SD) value of total testosterone was 15.92 (+ 6.322) nmol/L, while the mean (± SD) values of cholesterol, triglyceride, HDL and LDL were 182.71 (+ 40.673), 134.02 (+ 55.407), 41.37 (+ 8.018) and 118.13 (+ 33.451) mg/dl respectively. Statistically significant difference (P = 0.021) was observed in the mean value of serum triglyceride when compared with the two testosterone groups. Significant negative (P = 0.000) and positive (P = 0.001) association of testosterone with triglyceride and HDL respectively were also documented. Multivariable linear regression model showed significant decrease in triglyceride level by 2.742 mg/dl and significant increase in HDL level by 0.304 mg/dl for each additional nmol/L of age adjusted testosterone. Conclusion: Convincing negative and positive associations of total testosterone with triglyceride and HDL respectively in this study suggest a promising link between low total testosterone and obesity.